Detection of transient protein folding populations by mass spectrometry. - Miranker, A; Robinson, C; Radford, SE; Aplin, RT; Dobson, C (1993)
Hydrogen-deuterium exchange measurements are becoming increasingly important in studies of the dynamics of protein molecules and, particularly, of their folding behavior. Electrospray ionization mass spectrometry (ESI-MS) has been used to obtain the distribution of masses within a population of protein molecules that had undergone hydrogen exchange in solution. This information is complementary to that from nuclear magnetic resonance spectroscopy (NMR) experiments, which measure the average occupancy of individual sites over the distribution of protein molecules. In experiments with hen lysozyme, a combination of ESI-MS and NMR was used to distinguish between alternative mechanisms of hydrogen exchange, providing insight into the nature and populations of transient folding intermediates. These results have helped to detail the pathways available to a protein during refolding.